2019
DOI: 10.3389/fonc.2019.00456
|View full text |Cite
|
Sign up to set email alerts
|

IL-4/IL-13 Stimulated Macrophages Enhance Breast Cancer Invasion Via Rho-GTPase Regulation of Synergistic VEGF/CCL-18 Signaling

Abstract: Tumor associated macrophages (TAMs) are increasingly recognized as major contributors to the metastatic progression of breast cancer and enriched levels of TAMs often correlate with poor prognosis. Despite our current advances it remains unclear which subset of M2-like macrophages have the highest capacity to enhance the metastatic program and which mechanisms regulate this process. Effective targeting of macrophages that aid cancer progression requires knowledge of the specific mechanisms underlying their pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 47 publications
(51 reference statements)
2
64
0
Order By: Relevance
“…Regulates T cell recruitment under homeostatic and inflammatory conditions [5] G-CSF Controls the maturation of neutrophils [8] HGF Induces cancer cell migration and invasion, wound healing, angiogenesis [21] IL-1 beta Inhibits the proliferation of some cancers, amplifies the function of dendritic cells, stimulates the proliferation and differentiation of CD4, CD8 and natural killer (NK) cells, increases antibody production by lymphocytes B, and finally increases the expression of adhesion molecules on vascular endothelium [22] IL-12 Induction of Th1 cells [23,24] IL-13 Induces the activation of M2 macrophages, polarizes M2a macrophages and induces migration and invasion of breast cancer cells [25,26] [27,28] IL-8 Increased the formation of primary and secondary tumor spheres, as well as the cancer stem cell phenotype in BC [29] MCP-1 Increases monocyte mobilization and poor survival and is involved in monocyte polarization to M2-cells [30] MCP-3 Attracts monocytes, dendritic cells (DCs), and activated T lymphocytes, to invasion sites [31] MIF Induces myeloid-derived suppressor cells in tumor microenvironment [32] PDGF-beta Regulates metastasis and vascular remodeling in cancer [33]…”
Section: Ctackmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulates T cell recruitment under homeostatic and inflammatory conditions [5] G-CSF Controls the maturation of neutrophils [8] HGF Induces cancer cell migration and invasion, wound healing, angiogenesis [21] IL-1 beta Inhibits the proliferation of some cancers, amplifies the function of dendritic cells, stimulates the proliferation and differentiation of CD4, CD8 and natural killer (NK) cells, increases antibody production by lymphocytes B, and finally increases the expression of adhesion molecules on vascular endothelium [22] IL-12 Induction of Th1 cells [23,24] IL-13 Induces the activation of M2 macrophages, polarizes M2a macrophages and induces migration and invasion of breast cancer cells [25,26] [27,28] IL-8 Increased the formation of primary and secondary tumor spheres, as well as the cancer stem cell phenotype in BC [29] MCP-1 Increases monocyte mobilization and poor survival and is involved in monocyte polarization to M2-cells [30] MCP-3 Attracts monocytes, dendritic cells (DCs), and activated T lymphocytes, to invasion sites [31] MIF Induces myeloid-derived suppressor cells in tumor microenvironment [32] PDGF-beta Regulates metastasis and vascular remodeling in cancer [33]…”
Section: Ctackmentioning
confidence: 99%
“…M2 macrophages have also been implicated in tumor growth [42,43], and their presence has been correlated with a poor prognosis [44]. Recent data published by Little et al showed that IL-4/IL-13 polarizes M2a macrophages and induces migration and invasion of breast cancer cells [26]. Based on those findings, we can assume that IORT treatment may be beneficial not only but direct tumor cell killing but also in changing the tumor bed microenvironment, making it less favorable for tumor recurrence due to decreased concentration of tumor-facilitating cytokines.…”
Section: Rantesmentioning
confidence: 99%
“…The Rho-like family of Rho-GTPases have been well characterized for their participation in the progression of breast cancer 32,3436 and the alteration of metabolic phenotype 33 . Therefore, we next applied our imaging and analysis strategy to explore the potential for fragmented mitochondria in breast cancer cells that lack either the Rho-like family of Rho-GTPases RhoA or RhoC, via CRISPR/Cas9 knockout (WT, RhoA KO, RhoC KO) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, application of this strategy yielded insights into the role of Rho-GTPases in mitochondrial dynamics in breast cancer. While the roles of the Rho-like family of Rho-GTPases in breast cancer progression were well characterized, our study is the first to determine their role in the regulation of mitochondrial content, fragmentation, and respiratory capacity 3236 . Collectively this study enhances the utility of the metabolic flux assay and provides a more complete platform to study mitochondrial biology from multiple dimensions, simultaneously.…”
Section: Introductionmentioning
confidence: 98%
“…A highly reproducible assay allows for fewer experiments to be performed to arrive at convincing and robust conclusions, saving time and resources. This is particularly useful in the design of high value chemotherapeutics that aim to inhibit cancer metastasis or understand the relationship between genetic mediators of cancer cell migration or invasion; examples can be seen here (15,16).…”
Section: Introductionmentioning
confidence: 99%